2021
DOI: 10.3892/ijmm.2021.5023
|View full text |Cite
|
Sign up to set email alerts
|

Omega‑3 polyunsaturated fatty acids inhibit IL‑11/STAT3 signaling in hepatocytes during acetaminophen hepatotoxicity

Abstract: Omega-3 polyunsaturated fatty acids (n-3 PUFAs) exert a negative effect on IL-6 production in several liver disorders, including cirrhosis, acute liver failure and fatty liver disease. However, its effect on the production of IL-11, another important IL-6 family cytokine, remains unclear. IL-11 was found to be significantly elevated in acetaminophen (APAP)-induced liver damage. The aim of the present study was to investigate whether and how n-3 PUFAs modulate IL-11 production during APAP-induced liver injury. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…For instance, palmitic and stearic acids could be particularly harmful by promoting hepatic CYP2E1 induction [ 74 , 98 , 99 ], as previously mentioned. Furthermore, studies carried out in transgenic fat-1 mice, which endogenously convert n-6 PUFAs to n-3 PUFAs, showed that male animals were more susceptible to APAP-induced acute liver injury, possibly via a JNK-dependent mechanism and downregulation of signal transducer and activator of transcription 3 (STAT3) [ 109 , 110 ].…”
Section: Factors Modulating Apap Hepatotoxicity In Obesity and Nafldmentioning
confidence: 99%
“…For instance, palmitic and stearic acids could be particularly harmful by promoting hepatic CYP2E1 induction [ 74 , 98 , 99 ], as previously mentioned. Furthermore, studies carried out in transgenic fat-1 mice, which endogenously convert n-6 PUFAs to n-3 PUFAs, showed that male animals were more susceptible to APAP-induced acute liver injury, possibly via a JNK-dependent mechanism and downregulation of signal transducer and activator of transcription 3 (STAT3) [ 109 , 110 ].…”
Section: Factors Modulating Apap Hepatotoxicity In Obesity and Nafldmentioning
confidence: 99%
“…This mechanism was also at work in other tissues. Mitigation of acetaminophen toxicity by ω3FA depends on the inhibition of IL-11 expression and phosphorylation of ERK1/2, thus blocking hepatic injury [145]. In human breast cancer cells, DHA inhibits gremlin-1 (GREM1), thereby preventing the activation of the ERK/N-cadherin/Slug axis and partial EMT [146].…”
Section: The Role Of Omega-3 Fatty Acids In Counteracting Ckd Progres...mentioning
confidence: 99%
“…APAP highly induces IL-11 secretion by hepatocytes, and IL-11 deficient mice exhibit spontaneous liver repair [ 212 ], however some studies demonstrate that IL-11 expression has compensatory and cytoprotective effects [ 213 ]. Omega‑3 polyunsaturated fatty acids exacerbate AILI by modulating extracellular regulated protein kinases (ERK)1/2-mediated Fra 1 expression to inhibit the production of IL-11 and further activate downstream signal transducer and activator of transcription 3 (STAT3) in hepatocytes [ 214 ]. However, a recent study suggested that upregulated IL-11 drives APAP-induced hepatocyte death, and specific deleting IL-11RA1 in hepatocytes or IL-11 knockdown in mice protected against AILI [ 215 ].…”
Section: Role Of Inflammatory Mediators In Ailimentioning
confidence: 99%